Diversity of terrestrial gastropods in Diyala governorate, Iraq (Journal of Pharmaceutical Negative Results, 2022)
The current was conducted to identify the diversity of terrestrial gastropods in five sites in Diyala Governorate. Eight unite had been identified during October 2021 to May 2022.( Eobania vermiculata ، Monacha obstructa، Polygyra cereolus، Cochlicella Barbara ، Xeropicta Spp ، Theba pisana ، Trochulus hispidus ، Rumina decollate ، Deroceras spp. , population density and soil properties (temperature, pH, electrical conductivity, moisture, organic matter, calcium, soil texture) had been studied. the results of the study also showed a spatial and temporal variation in the distribution of gastropods, where M. obstructa was recorded as the dominant species in all sites, while Deroceras spp, recorded as a rare species. the results of the Shanon-Weiner Diversity Index ranged between (0-1.093)bit. Ind -1, the Species richness index ranged between (0 -0.832), as Al- Khalis district site recorded as the richest in species among the five sites, and the Evenness index ranged (0 - 0.788) as the Khanaqin distract site was more evenness than other sites